Rising strong the reckoning, the rumble, the revolution - Brown, Brene (New York Spiel and Grau., 2015)
Social scientist Bren B̌rown has ignited a global conversation on courage, vulnerability, shame, and worthiness. Her pioneering work uncovered a profound truth: Vulnerability?the willingness to show up and be seen with no guarantee of outcome?is the only path to more love, belonging, creativity, and joy. But living a brave life is not always easy: We are, inevitably, going to stumble and fall.
Includes index
Keywords: Self-actualization (Psychology)